CCCTC-binding factor-mediated microRNA-340-5p suppression aggravates myocardial injury in rats with severe acute pancreatitis through activation of the HMGB1/TLR4 axis. (4th May 2022) - Gao, Yazhou; Gao, Yanxia; Niu, Zequn; Liu, Jie; Feng, Hui; Sun, Jiangli; Wang, Liming; Pan, Longfei
Abstract: Background: Severe acute pancreatitis (SAP) is a life-threatening disorder associated with multisystem organ failure. This study aimed to investigate the function of high mobility group box 1 (HMGB1) in SAP-induced myocardial injury. Methods: A rat model with SAP was induced. The pathological changes in rat pancreatic and cardiac tissues were examined by HE staining. Cardiomyocyte apoptosis in rat cardiac tissues, and the serum levels of myocardial injury markers and pro-inflammatory cytokines were examined. Rat primary cardiomyocytes were treated with H2 O2 for in vitro experiments. The regulatory molecules of HMGB1 were predicted by bioinformatics analysis. Altered expression of HMGB1, microRNA (miR)-340-5p and CCCTC-binding factor (CTCF) was introduced in rats or cells to investigate their roles in myocardial injury. Results: CTCF and HMGB1 were highly expressed but miR-340-5p was poorly expressed in cardiac tissues of rats with SAP. HMGB1 silencing reduced toll-like receptor 4 (TLR4) expression to promote proliferation and reduce apoptosis of H2 O2 -treated cardiomyocytes. miR-340-5p targeted HMGB1 mRNA, while CTCF suppressed miR-340-5p transcription. CTCF upregulation or miR-340-5p downregulation blocked the effects of HMGB1 silencing on cardiomyocytes. In vivo, CTCF silencing alleviated injury in rat pancreatic and cardiac tissues and reduced the expression of creatine kinase-MB (CK-MB), lactic dehydrogenase, interleukin (IL)-1β, IL-6 and tumor necrosis factor-α (TNF-α) in rat serum. But further overexpression of HMGB1 or inhibition of miR-340-5p aggravated the symptoms in rats. Conclusion: This study demonstrated that CTCF reduces transcription of miR-340-5p to promote HMGB1 expression, which activates TLR4 expression and promotes myocardial injury in rats with SAP.